A fern AINTEGUMENTA gene mirrors BABY BOOM in promoting apogamy in Ceratopteris richardii. (8th March 2017) - Bui, Linh T.; Pandzic, Dzevida; Youngstrom, Christopher E.; Wallace, Simon; Irish, Erin E.; Szövényi, Péter; Cheng, Chi‐Lien
Summary: Asexual reproduction is widespread in land plants, including ferns where 10% of all species are obligate asexuals. In these ferns, apogamous sporophytes are generated directly from gametophytes, bypassing fertilization. In the model fern Ceratopteris richardii, a sexual species, apogamy can be induced by culture on high sugar media. BABY BOOM ( BBM ) genes in angiosperms are known to promote somatic embryogenesis, which like apogamy produce sporophytes without fertilization. Here, a Brassica napus BBM ( BnBBM ) was used to investigate genetic similarity between apogamy in ferns and somatic embryogenesis in angiosperms. A C. richardii transcriptome was constructed from which one AINTEGUMENTA‐LIKE unigene, CrANT, was identified. Whole mount in situ hybridization showed that CrANT is expressed in sperm and fertilized eggs. Phylogenetic analysis grouped CrANT with other non‐seed‐plant ANT genes to the euANT clade but in a branch separate from BBM genes. Overexpression of CrANT or BnBBM promotes apogamy in C. richardii without sugar supplement. CrANT knockdown gametophytes responded weakly to sugar for apogamy promotion. Theses results suggest some genetic conservation between apogamy and somatic embryogenesis and that such asexual reproduction may be ancient. Significance Statement: Asexual reproduction is widespread in land plants; somatic embryogenesis can form new sporophytes, and many non‐seed plants, especially ferns, develop sporophytes directly from gametophytes without fertilization, through a process called apogamy. Here we uncover a genetic similarity between somatic embryogenesis and apogamy, by showing that apogamy in a model fern is promoted by expression of an angiosperm gene that promotes somatic embryogenesis.